Highly effective, repetitive nanosecond-range ka-band BWO - Yalandin M. I.; Rukin S. N.; Shpak V. G.; Shunailov S. A.; Rostov V. V.; Mesyats G. A. Gennady Andreyevich (2008, 2008)
В фонде НТБ ТПУ отсутствует